Integrated Transcriptomics and Metabolomics Analysis Reveal Key Metabolism Pathways Contributing to Cold Tolerance in Peanut - Wang, Xin; Liu, Yue; Han, Zhongkui; Chen, Yuning; Huai, Dongxin; Kang, Yanping; Wang, Zhihui; Yan, Liying; Jiang, Huifang; Lei, Yong; Liao, Boshou (Frontiers in Plant Science, 2021)
Low temperature (non-freezing) is one of the major limiting factors for peanut (Arachis hypogaea L.) growth, yield and geographic distribution. Due to the complexity of cold-resistance trait in peanut, the molecular mechanism of cold tolerance and related gene networks were largely unknown. In this study, metabolomic analysis of two peanut cultivars subjected to chilling stress obtained a set of cold-responsive metabolites, included several carbohydrates and polyamines. These substances showed higher accumulation pattern in SLH (cold-resistant) than ZH12 (cold-susceptible) peanut cultivar under cold stress, indicating their importance in protecting peanut from chilling injuries. In addition, 3620 Core Cold Tolerance Genes (CCTGs) were identified by transcriptome sequencing, and the CCTGs were most significant enriched in “phenylpropanoid biosynthesis” pathway. Two vital modules and several novel hub genes were obtained by weighted gene co-expression network analysis (WGCNA). The expression levels of structure genes involved in soluble sugar, polyamine and G-lignin biosynthetic pathways substantially increased in parallel with metabolite accumulation profiles in response to cold stress, suggesting they might be crucial contributors during the adaptation of peanut to low temperature. These findings will not only provide valuable resources for study of cold resistance in peanut, but also lay a foundation for genetic modification of cold regulators to enhance stress tolerance in crops.